Hyperbolic Discounting in Fiscal Policy: The Case of Malaysian Government Budget - Putri Swastika; Azura Othman (The Postgraduate of Institut Agama Islam Negeri Metro Lampung, 2019)
Thispaper examines the lag effect of interest payments on the national output represented by GDP. The lag effectimplies the observation of hyperbolic discounting in the fiscal policy. The idea is round-eyed;that the government takes on high debts to finance their spending while not factoring or placing less importanceon the cost of the interest payments. The concept of hyperbolic discounting of behavioral economics is used in this paper to explain this phenomenon in the present path of public policy which operates under an interest-based system. We conduct this analysis by examiningthe present fiscal model and its effect on the economy, wherein debt is preferredin fiscal policy framework.It appears from the findings that the trend in Malaysia’s fiscal policy shows the presence of hyperbolic discounting.Shifting the debt burden to future governments and spending above revenue capacity can be seen as a manifestation of the common pool problem. Two main policy recommendations can be made. Firstly, the fiscal policy structure has to move away from the current interest-based borrowing. This is because an intrinsic feature of the interest-based system is that the risks of a debt transaction are transferred from the lender to the borrower.Secondly, the current tax structure can be simplied to improve tax compliance so as to improve tax revenue collection.Both the above policy recommendations have the potential of reducing the effect of hyperbolic discounting. The first increases the interaction between the government and the public thus enhances the governance structure of the government. The government will have to be more transparent in its dealing as the public has a vested interest in the development projects. The second enhances the first effect by providing a potential increase in tax revenue which will reduce the stress on debt servicing and the need for borrowing.